Prevalence and Severity of Postdialysis Fatigue Are Higher in Patients on Chronic Hemodialysis With Functional Disability. Issue 6 (4th July 2018) - Bossola, Maurizio; Di Stasio, Enrico; Sirolli, Vittorio; Ippoliti, Fabio; Cenerelli, Stefano; Monteburini, Tania; Parodi, Emanuele; Santarelli, Stefano; Nebiolo, Pier Eugenio; Bonomini, Mario; Picca, Anna; Calvani, Riccardo; et al.
Abstract: The aim of the present study was to determine the intensity, duration, frequency and prevalence of postdialysis fatigue (PDF) in patients on chronic hemodialysis (PCD) with and without functional disability. Patients underwent assessment of functional ability by the Katz ADL (activity daily living) questionnaire and the Lawton and Brody scale for the instrumental activity daily living (IADL) fatigue using the SF‐36 Vitality Subscale, comorbidity through the Charlson comorbidity score index (CDI), and time of recovery after hemodialysis (TIRD). We studied 271 PCD. ADL and IADL disabilities were present in 75 (27.6%) and 168 (62%) patients, respectively. Patients with ADL disability were significantly older and showed higher CDI scores, and lower levels of serum albumin and Kt/V. Prevalence of PDF was significantly higher in patients with ADL disability as well as its severity, intensity, duration and frequency. Patients with IADL disability were significantly older, had a higher CCI score, had lower levels of serum albumin and Kt/V, and had a higher severity, intensity, duration and frequency of PDF. At multivariate regression analysis, ADL disability was positively associated with age, prevalence and severity of PDF, and dialysate temperature and inversely associated with serum albumin levels. IADL disability was instead positively associated with age and dialysate temperature and inversely associated with serum albumin levels. In conclusion, prevalence and severity of PDF are significantly higher in PCD with ADL disability than in those without it. This knowledge may have important implications for the development of interventions to reduce PDF in PCD.